Localized Pigmented Villonodular Synovitis of the Hip: Sudden-Onset Pain Caused by Torsion of the Tumor Pedicle - Kiyokazu Fukui; Ayumi Kaneuji; Eriko Kinoshita; Yuhei Numata; Takayuki Nojima; Tadami Matsumoto (Case Reports in Orthopedics)
Pigmented villonodular synovitis is a rare, benign, but potentially locally aggressive disease that should be considered in younger patients who present with monoarticular joint symptoms and pathology. We present the case of a 33-year-old woman with a mass arising from her right hip joint that was examined using a multimodal radiological approach. Because her clinical presentation mimicked that of synovial osteochondromatosis of the hip, surgical dislocation was performed. Histopathological examination of the resected specimen confirmed the diagnosis of localized pigmented villonodular synovitis, with the mass consisting of proliferation of fibrohistiocytic cells, abundant hemosiderin, foamy histiocytes, and occasional giant cells. Because of the presence of tumor necrosis, we hypothesize that torsion of the tumor pedicle was the cause of acute presentation.